TINJAUAN YURIDIS PEMELIHARAAN TAMAN KEANEKARAGAMAN HAYATI DIKAWASAN INDUSTRI KIIC SEBAGAI BAGIAN DARI KONSEP PEMBANGUNAN BERKELANJUTAN BERDASARKAN SURAT KEPUTUSAN BUPATI KARAWANG NOMOR : 188/ Kep.370 -Huk/ 2014 TENTANG TAMAN KEANEKARAGAMAN HAYATI TELAGA DESA DI KAWASAN INDUSTRI KIIC KABUPATEN KARAWANG - Herfady Raiza Tifarani; Teuku Syahrul Ansari (Universitas Labuhanbatu, 2023)
Karawang Regency is one of the districts with the highest level of rice productivity in West Java. The shift in development patterns and policies that are more directed towards the real sector has resulted in the transfer of land use functions in this district. This can be seen by the growing development of Karawang as one of the cities with a large number of industrial areas in Indonesia (such as Karawang International Industrial City/KIIC, Suryacipta, and others). Factory waste contained in this industrial area can cause environmental pollution that can disrupt the balance of ecosystems in nature. As one of the implementations of the community's economic awareness program as well as a means of improving business capabilities, especially those based on agriculture (agribusiness) for surrounding villages, KIIC together with companies in the KIIC Industrial Estate have created a joint CSR (Corporate Social Responsibility) program that called the Village Lake. The presence of the Village Lake has a positive impact on the environment around the KIIC industrial area because the presence of the village lake can provide jobs for local residents who do not have jobs. Telaga Desa is a joint CSR (Corporate Social Responsibility) program carried out by KIIC and the companies operating in it. This program aims to build a harmonious relationship with residents around the KIIC industrial area, to become an information center for CSR (Corporate Social Responsibility) activities carried out by companies operating in the KIIC industrial area, to help develop economic growth and opportunities for the surrounding community that are appropriate. with a background of expertise, become an agribusiness training center for local communities and company employees, become a place for conservation of rare plants and encourage nature conservation activities through tree planting and the use of simple technology that is environmentally sound.Keywords: industrial area, biodiversity, effort, impact.